High frequency transformer modelling using state space representation for FRA studies - Abu-Siada, Ahmed (2017)
The concept of Frequency Response Analysis (FRA) has been widely accepted as a reliable diagnostic tool to detect winding and core deformations within power transformers. While the measurement of transformer FRA signatures has been standardized since the development of advanced frequency response analyzers, interpretation of the FRA signature which is provided as a graphical plot is still challenging. At this stage there is no interpretation code for FRA signatures published and widely accepted yet. To develop such codes, impact of various mechanical deformations on the FRA signature must be well investigated and fully understood through simulation analysis and practical measurement. For simulation analysis, a reliable high frequency transformer model is essential. This paper presents a state space representation for high frequency transformer model in which the physical meaning of the model parameters facilitates identification of the problem within the transformer. Various mechanical faults are simulated into the model to investigate their impacts on the FRA signature.